2016
DOI: 10.1088/0953-2048/30/1/015001
|View full text |Cite
|
Sign up to set email alerts
|

Non-perturbative measurement of low-intensity charged particle beams

Abstract: Non-perturbative measurements of low-intensity charged particle beams are particularly challenging to beam diagnostics due to the low amplitude of the induced electromagnetic fields. In the low-energy antiproton decelerator (AD) and the future extra low energy antiproton rings at CERN, an absolute measurement of the beam intensity is essential to monitor the operation efficiency. Superconducting quantum interference device (SQUID) based cryogenic current comparators (CCC) have been used for measuring slow char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…3 [16]. These are the first CCC beam current measurements performed in a synchrotron using both, coasting and short-bunched beams.…”
Section: Cryogenic Current Comparatormentioning
confidence: 95%
“…3 [16]. These are the first CCC beam current measurements performed in a synchrotron using both, coasting and short-bunched beams.…”
Section: Cryogenic Current Comparatormentioning
confidence: 95%
“…Ring shield CCCs are commonly applied in diagnostic devices of particle beams in accelerator facilities [9][10][11][12]. shielding configuration exhibits an interleaved comb-like meander structure along the axial direction, as depicted in Figures 12 and 13.…”
Section: Review Of the Ring Shieldmentioning
confidence: 99%
“…In this work, we investigate the performance of a folded coaxial shield (depicted in Figures 1b and 1c), which is, to the best of our knowledge, studied here for the first time. This shield configuration is compared to the ring structure (depicted in Figure 1a) found in several CCCs dedicated to the diagnostics of particle beams in accelerator facilities [9][10][11][12]. In this comparison, the shields geometries are constrained by the radius of the beam tube and the cross-sectional area of the CCC pickup core.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experiments have shown that even the white noise is limited by dissipative effects in the core material. Moreover, a tight coupling of the input coil comes along with a large susceptibility to disturbances as well as huge demands on the dynamic range and current slew-rate of the beam monitor [9].…”
Section: Beam Monitor Concept and Designmentioning
confidence: 99%